Structure, nanomechanics, and dynamics of dispersed surfactant‐free clay nanocomposite films. Issue 8 (22nd February 2018) - Zhang, Xiao; Zhao, Jing; Snyder, Chad R.; Al‐Enizi, Abdullah; Eltazahry, Ahmed; Simmons, David S.; Karim, Alamgir
Abstract : The current work presents a new approach to achieve high quality dispersion of surfactant‐free nanoclay tactoid particles in sub‐micron thin films despite the absence of organic modifier. Natural Montmorillonite particles, N a + Cloisite, were dispersed in thin films of polycaprolactone (PCL) through a flow coating technique assisted by ultra‐sonication. Wide‐angle X‐ray scattering (WAXS), grazing‐incidence wide‐angle X‐ray scattering (GI‐WAXS), and transmission electron microscopy (TEM) were used to confirm the level of natural clay dispersion down to the level of tactoids (sub‐micron scale stacks of clay sheets). These characterization techniques were carried out in conjunction with an analysis of nanomechanical properties via strain‐induced buckling instability for modulus measurements (SIEBIMM), a high‐throughput technique to characterize thin film mechanical properties. The buckling patterns indicate that the natural clay tactoids separate buckling‐enhancing (high‐modulus) crystalline regions and interconnect buckling‐suppressing amorphous (low‐modulus) regions. Due to the tactoid length scale, the glass transition behavior of the composites as characterized by broadband dielectric relaxation spectroscopy was unmodified by the clay. Likewise, the glass transition temperature, T g, and fragility (slope of relaxation time behavior approaching T g ), remain unaffected, indicating that these dispersed tactoids do not induce pronounced confinement effects on dynamics. POLYM. ENG. SCI., 58:1285–1295, 2018. © 2018 Society of Plastics Engineers